Archimorphic and Neomorphic Skull Traits: Analysis of Intercorrelation - Bielicki, Tadeusz; Miszkiwicz, Brunon (Anthropological Review, 1987)
The following question was posed: do the craniometric traits in modern man in which the distinction between archimorphism and neomorphism is expressed have a tendency to occur as a complex whole? Does variability of cranial shapes observed today includes, as one of its components, the opposition: "archaic type of morphology - modern type of morphology”? To find answers to these questions two analyses were carried out of the material of a sample of 200 male crania from the Milicz cemetery (13th century). 1. The matrix of correlation coefficients between 25 measures of shape (rations and angles) and 4 measures of size was analyzed. It was found that the shapes of topographically different parts of the cranium (eg. forehead and occiput) as well as different aspects of cranial shape (eg. degree of globularity of the brain case in the sagittal and frontal plane) are largely independent of one another. 2. The matrices of correlation coefficients calculated separately for 25 diameters and angles of the braincase and 16 diameters and angles of the face were analysed by means of Hotelling’s principal component analysis. It was found that in both cases no principal component emerged which could be interpreted as an axis of variation expressing the opposition "multi-trait archimorphism- multi-trait neomorphism" (though the first principal component for the face is close to that meaning). The above results have the following implications for paleotaxonomy: 1) Fossil skulls exibiting mosaic combinations of "archaic" and "modern" traits (eg. Fetralona, Amud, Steinheim, Sale) should evoke less surprise than they usually have; such "disharmonious" combinations are to be expected as products of random assortment of independent and highly variable morphological traits. 2) For the same reason less surprise should be evoked by fragmentary finds which appear more "modern", (or more "archaic") than it might be expected from their geological age or stratigraphical placement (eg. the Swanscombe occiput, the Fontechevade frontal fragment). In many such cases the remaining (missing) parts of the skull did not have to be equally "modem" (or "archaic") as the preserved fragment. Both these situations may be explicable in terms of normal within-species variation and do not necessite explanations based on hypotheses about hybridization or the co-existence, during a given period of time, of two evolutionary lines of hominids, one "advanced" and the other "retarded”.